2022
DOI: 10.1093/heapol/czac015
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of iron and folic acid supplementation in India: progress under the Anemia Mukt Bharat strategy 2017–20

Abstract: High prevalence of anemia is a severe public health problem in India. In 2018, India launched the Anemia Mukt Bharat (AMB) strategy that focuses on six beneficiary groups for coverage, six institutional mechanisms for health system strengthening and six programmatic interventions to accelerate reductions in anemia prevalence. This paper uses the Health Management Information System (HMIS) data (2017–18 to 2019–20) to examine gains in IFA coverage across Indian states. A coverage based AMB index is computed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…The National Iron Plus Initiative (NIPI) of India recommends that every pregnant woman should consume 100 mg of elemental iron and 500 mcg of folic acid daily for 100 days during pregnancy. Also, the current Anaemia -Mukt Bharat (Anaemia-Free India), a strategy launched in 2018, aims to achieve the targets of POSHAN Abhiyaan (POSHAN: Prime Minister’s Overarching Scheme for Holistic Nutrition Mission), has taken every possible initiative to attain reduction of prevalence of maternal and child anaemia by three percentage points per year 41 . Therefore, finding of this study is consistent with the recommendation of IFA consumption to increase maternal and infant survival.…”
Section: Discussionmentioning
confidence: 99%
“…The National Iron Plus Initiative (NIPI) of India recommends that every pregnant woman should consume 100 mg of elemental iron and 500 mcg of folic acid daily for 100 days during pregnancy. Also, the current Anaemia -Mukt Bharat (Anaemia-Free India), a strategy launched in 2018, aims to achieve the targets of POSHAN Abhiyaan (POSHAN: Prime Minister’s Overarching Scheme for Holistic Nutrition Mission), has taken every possible initiative to attain reduction of prevalence of maternal and child anaemia by three percentage points per year 41 . Therefore, finding of this study is consistent with the recommendation of IFA consumption to increase maternal and infant survival.…”
Section: Discussionmentioning
confidence: 99%
“…children (6-59 months), adolescent girls (15-19 years), adolescent boys (10-19 years), women of reproductive age (WRA), pregnant women and lactating mothers. The AMB programme for IFA supplementation serves 26 million pregnant women, 13 million lactating mothers, and 73 million school-age children and adolescents (5-19 years) and 17 million children under of 5-69 months [9].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials demonstrated that weekly oral iron and folic acid supplementation was as effective as daily supplementation in iron deficiency anemia patients, with fewer side effects and better compliance ( 6 , 7 ). The administration of iron tablets in adolescence is also beneficial to improve the status of anemia and increase iron stores in the early stages of pregnancy ( 8 ).…”
Section: Introductionmentioning
confidence: 99%